Optimization of Digital Branding and Entrepreneurial Spirit to Enhance Youth Employment in Gig Economy Era - Suryadi, Nanang; Firdausiah, Rr Ayu; Islam F, Muhammad Fajrul; Huda, Choirul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
This community service program aims to enhance youth employability in rural areas by equipping participants with practical skills in digital personal branding and entrepreneurial mindset. Implemented in Desa Tegalweru, the training followed a structured four-phase approach: self-assessment using SWOT analysis, brand positioning, LinkedIn optimization, and freelance platform registration. Through participatory action methods, 30 youth participants identified their strengths, weaknesses, opportunities, and threats to build authentic personal brands and explore digital work opportunities. The program resulted in 20 optimized LinkedIn accounts, increased motivation for career development, and improved readiness to engage in the gig economy. Participants demonstrated a shift from passive job-seeking to proactive digital participation. The initiative addressed digital skill gaps while fostering local innovation and inclusive economic engagement through collaboration with village institutions